Mother's Employment Status With Fine Motor Development - Yusni Podungge; Endah Yulianingsih Adam; Yusni Igirisa; Hasnawaty Surya Porouw; Rifkawati Mohamad (Universitas Aisyah Pringsewu, 2021)
According to WHO, 5-25% of pre-school age children suffer from minor brain dysfunction including impaired fine motor development of children. The age of 5 years is a good period for motoric development of children, especially gross motor development, meanwhile, the age of 4-6 years is a golden period for the development of fine motor skills of children. Children aged 4-6 years can understand and grasp what is directed by the mother so That the child can easily interect and build social relationship.This study aims to determine the relationship between maternal employment status and fine motoric development of children aged 4-6 years in Mentari PAUD. The research method used was an analytic survey with a cross sectional study design. The research instruments were questionnaires, developmental pre-screening sheets and the development pre-screening sheet (KPSP).The results of statistical tests using Chi-Square obtained that the value of X2 was calculated as the value of p = 0.028 (p less than 0.05). In conclusion, there is a significant relationship between maternal employment status and fine motoric development of children. The suggestions for families are expected to be able to help parents in stimulating children when the mother or child's parents are working. Abstrak: Menurut WHO, 5-25% anak usia pra sekolah menderita disfungsi otak ringan termasuk gangguan perkembangan motorik halus anak. Usia 5 tahun merupakan masa yang baik untuk perkembangan motorik anak khususnya perkembangan motorik kasar, sedangkan usia 4-6 tahun merupakan masa emas bagi perkembangan motorik halus anak. Anak usia 4-6 tahun dapat memahami dan memahami apa yang diarahkan oleh ibu sehingga anak dapat dengan mudah berinteraksi dan membangun hubungan sosial. Penelitian ini bertujuan untuk mengetahui hubungan status pekerjaan ibu dengan perkembangan motorik halus anak usia 4-6 tahun di PAUD Mentari. Metode penelitian yang digunakan adalah survei analitik dengan desain studi cross sectional. Instrumen penelitian berupa angket, lembar pra-screening perkembangan dan lembar pra-screening pengembangan (KPSP). Hasil uji statistik dengan menggunakan Chi-Square diperoleh nilai X2 yang dihitung dengan nilai p = 0,028 (p kurang dari 0,05). Kesimpulannya, ada hubungan yang signifikan antara status pekerjaan ibu dengan perkembangan motorik halus anak. Saran bagi keluarga diharapkan dapat membantu orang tua dalam merangsang anak ketika ibu atau orang tua anak bekerja.